Implementasi Supervisi Akademik dan Manajemen Sarana Prasarana dalam Meningkatkan Mutu Pembelajaran Al-Qur'an Hadits - Rohmawati; Abdullah Hadziq (Fahima, 2023)
This study aims to determine the implementation of academic supervision and infrastructure management in order to improve the quality of learning the Qur'an Hadith. The research carried out is research that seeks to reveal, find and explore information about the Implementation of academic supervision and infrastructure management. This research uses a qualitative approach, namely research aimed at describing and analyzing phenomena, events, social activities, attitudes, perceptions, and thoughts of people individually and in groups. The results showed that the implementation of academic supervision and infrastructure management can improve the quality of learning al-Qur'an Hadith in MTsN 6 Sragen very well. Application of academic supervision includes the process of planning, implementing, evaluating and following up, and reporting.  Ensure infrastructure management by carrying out five stages of management, namely planning, procurement of goods, use and maintenance, inventory, and elimination.